ESTIMASI KARBON TERSIMPAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) VARIETAS SOCFINDO PADA KELAS KESESUAIAN LAHAN S3 DI KEBUN AEK TOROP PTPN III - Havier Situmorang; Aris Sukariawan; Aulia Juanda Djaingsastro; Mardiana Wahyuni (Jurnal Agro Estate, 2019)
The expansion of oil palm plantations has led to debate over the negative impacts on soil fertility, hydrology, biodiversity and global warming. Climate change occurs due to changes in the composition of the atmosphere, mainly due to an increase in the concentration of greenhouse gases (GHGs). The usefulness of photosynthesis using CO2 is important to note. The purpose of this study is to measure / estimate the stored carbon absorbed by the 13-year-old Socfindo palm oil plant in the land suitability class S3. The study was conducted in May to June 2019 at PT Aek Torop Kebun III. Using descriptive design with Destructive and Non-Destructive methods based on ICRAF. The parameters are Above Surface Biomass (BAP) and Substance Biomass (BTB). The results showed that the oil palm surface surface biomass (BAP) at the age of 13 years was 117,855 tons / ha. The results of observations of Undergrowth Biomass (BTB) are 0.392 Ton / ha, the potential carbon stored is 54.394 Ton C / Ha and carbon dioxide absorption is 199.625 Ton CO2 / Ha.